The Analysis of Conformity of Proliferation Security Initiative Rules with International Law - Mehdi Hatami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present article, the analytical research conducted in an analytical-descriptive manner, seeks to answer the question of Conformity of The Proliferation Security Initiative (PSI) with the Treaty law and customary international law. As one of the most important restrictive arrangements for the rights of developing countries in the field of advanced technologies, critics of the PSI believe that the intention of the members of the PSI to seize ships in the high sea and territorial waters violates the principle of freedom of the high seas and the right of innocent passage in territorial waters. In addition, the practices conducted in the framework of this initiative violate the right to self-defense and Security Council resolutions such as 1718 and 1540. On the other hand, the nature and manner of joining the initial operations and statistics about the success of its operations are vague and distorted. The finding of this article is that regardless of the justifications and support formed by this initiative, such an arrangement cannot be considered in conformity with treaty law and customary international law as well as the Security Council resolutions. The Proliferation Security Initiative is an illegal arrangement worthy of persistent objection, non-recognition and tries to prevent it from becoming the customary rule of international law.